The Development of Local Wisdom-Based Contextual Social Science Teaching Materials with The Theme of Indahnya Kebersamaan (The Beauty of Togetherness) for The Fourth Grade Level of Elementary School - Ilmiyah, Rosikhatul; Wasino, Wasino; Utomo, Udi (Universitas Negeri Semarang, 2019)
The learning process of Social Science (IPS) in Elementary School has not been yet optimum because teachers lacked knowledge about the contextual approach, had limited learning resources, namely teaching materials as well as the inability to develop teaching materials. Therefore, this study attempted to produce Central Java local wisdom-based contextual Social Science teaching materials with the theme of Ã¢â‚¬Å“Indahnya KebersamaanÃ¢â‚¬Â (The Beauty of Togetherness) for the fourth grade level of Elementary School (SD). This study employed Research and Development (R & D) method with the trial design of pre-test and post-test control group. Meanwhile, the data analysis technique used to examine the effectiveness of the teaching materials was N-Gain test by comparing pre-test and post-test scores of the experimental class and the control class. Further, the results of this study showed that: (1) there was a need on the development of Social Science teaching materials which could be used as learning resources to improve the Social Science learning quality in Elementary School. Additionally, the developed teaching materials were declared valid by having the average score of 84.38 with very valid criterion and very well applicable, (2) the characteristics of the developed teaching materials contained 7 components of the contextual approach which utilized Central Java local wisdom, and (3) the effectiveness test of the teaching materials showed that the experimental class achieved higher cognitive learning outcome with the N-Gain value of 0.46 than the control class of 0.19. In conclusion, the developed teaching materials can be used by teachers and students as learning resources in the learning process of Social Science to improve its quality.